P330 A CASE OF SEVERE AORTIC STENOSIS IN A YOUNG PATIENT WITH BICUSPID AORTIC VALVE, FAMILIAL HYPERCHOLESTEROLEMIA AND CALCIFICATION AT THE SINOTUBULAR JUNCTION. (18th May 2022) - Brusamolino, M; Muratori, M; Apostolo, A; Mapelli, M; Bonalumi, G; Nanci, G; Werba, J; Pepi, M; Mantegazza, V; Calligaris, G; Formenti, A; Agrifoglio, M; et al.
Abstract: Background: Familial hypercholesterolemia (FH) is a disorder characterized by elevated LDL–C and premature vascular calcifications. Aortic stenosis (AS) is the most frequent complication of bicuspid aortic valve (BAV), often requiring aortic valve replacement. Cardiac surgery in patients with severely calcified ascending aorta is challenging. Case Presentation: A 28 year old male from Albania presented to the ED for dyspnea and low–threshold angina. The patient had family history for CAD and a sister with known FH treated with PCSK9–i. He had BAV, known hypercholesterolemia (max cholesterol 660 mg/dL), treated since 2015 with rosuvastatin plus ezetimibe, with reported irregular intake. He was treated with PCI and bioresorbable vascular scaffold on LAD coronary artery. He underwent surgical removal of limb xanthomas. At admission, the patient was asymptomatic at rest. Cardiac auscultatory findings included an ejection murmur in the aortic area. He presented upper and inferior eyelid xanthelasmas, bilateral calcaneal tendon thickening, elbows and knee xanthoma removal scars. Blood tests were unremarkable, except for lipid profile (LDL–C 443 mg/dL, HDL 36 mg/dL, TG 73 mg/dL). The echocardiography showed BAV, severe AS (Vmax 4, 2 m/s, MPG 41 mmHg, AVA 0.46 cm2/m2), EF 60%. A coronary angiography excluded significant stenosis in the epicardial coronary vessels. An aortic CT scan showed sinotubular junction with preserved diameters and severe multiple parietal calcifications, ascending aorta with diffuse atheromatous disease. The patient underwent mechanical aortic valve replacement, ascending aorta thromboendarterectomy, non–coronary sinus enlargement patch, double CABG (SVG–OM, SVG–LAD) due to diffuse hypokinesia of the left ventricle after the interruption of extracorporeal circulation. At a 3–month outpatient re–evaluation, due to the unsatisfactory response to the regular intake of rosuvastatin plus ezetimibe (TC 309 mg/dL, TG 52 mg/dL, HDL 34 mg/dL, LDL–C 264 mg/dL), a PCSK9–i was prescribed. Genetic studies for FH are ongoing. Discussion: This case underlines the importance of aortic evaluation before aortic valve replacement, even in young FH patients, in which severe aortic calcification can influence surgical approach. Conclusion: We described the multidisciplinary management of a severe symptomatic AS in a young male with FH and sinotubular junction parietal calcifications, which represented a challenging substrate for valve replacement.